Consumer Preferences in Choosing Payment Methods on the TikTok Shop and Shopee Platforms - Nurlaila, Fitria; Kusmiati , Eti; Shiddieq , Diqy Fakhrun (Manunggal Halim Jaya, 2026)
The development of digital technology has changed consumer behavior in choosing payment methods on e-commerce platforms. This study involved 100 respondents who have used the PayLater and Cash on Delivery (COD) payment methods at TikTok Shop and Shopee, to compare consumer preferences for the two payment methods using the Analytical Hierarchy Process (AHP) method. The four main criteria analyzed include convenience, security, ease, and trust, with sub-criteria such as customer protection, transaction security, payment flexibility, and service reliability. The results show that consumers prefer the COD payment method at Shopee compared to other methods on both platforms. This is due to the better security, trust, and ease of transaction factors at Shopee. The urgency of this research stems from the increasing competition among e-commerce platforms and the need to understand consumer preferences when choosing payment methods, thereby providing strategic insights for platform managers to optimize their services. As such, Shopee is still the more dominant platform in meeting consumer needs regarding cash-on-delivery payment methods.